The pseudoscorpion genus Verrucachernes (Pseudoscorpiones: Chernetidae) in the Indian region - Romero-Ortiz, Catalina; Harvey, Mark S. (Zootaxa, 2019)
The pseudoscorpion genus Verrucachernes Chamberlin, 1947 is widely distributed in the Old World tropics, with three named Australasian and West Pacific species and two from Africa. A review of some pseudoscorpions described from India has revealed that Withius parvus Beier, 1930 (currently in the genus Metawithius) and Pselaphochernes indicus Beier, 1974 are misplaced and actually belong to the genus Verrucachernes Chamberlin, 1947, forming the new combinations V. parvus (Beier, 1930) comb. nov. and V. indicus (Beier, 1974) comb. nov., respectively. Both species possess the single, large, rounded spermatheca and other features typical of Verrucachernes.